2008
DOI: 10.1111/j.1440-172x.2008.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and management of infants' pain by mothers in Ile Ife, Nigeria

Abstract: Mothers' knowledge and management of pain in infants were assessed in this study. A total of 130 mothers from two health centres in Ile Ife, Southwest, Nigeria were selected by systematic sampling method. Only 3.8% indicated that neonates experience pain. Malaria (46.2%) was the major cause of pain identified. Analgesic/antimalarials (56.9%) and breastfeeding (16.9%) are used in pain relief. To improve the quality of life of infants, mothers must be educated on the assessment, early detection and management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In Nigeria, more potent analgesics were deemed too expensive for the average family to afford, which was attributed to a high rate of hospitalisation due to sickle cell pain 25. Due to the unaffordable cost of EMLA cream19 or ‘stronger’18 analgesics, non-pharmacological methods including breastfeeding, massage, eye contact, skin-to-skin contact and oral glucose were emphasised as pain-relieving measures amongst neonates undergoing surgery in several localities 18 19. Symptoms of persistent pain were identified in children breastfed with or without glucose14 16 and in children administered paracetamol12 16 18 27 and pentazocine (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In Nigeria, more potent analgesics were deemed too expensive for the average family to afford, which was attributed to a high rate of hospitalisation due to sickle cell pain 25. Due to the unaffordable cost of EMLA cream19 or ‘stronger’18 analgesics, non-pharmacological methods including breastfeeding, massage, eye contact, skin-to-skin contact and oral glucose were emphasised as pain-relieving measures amongst neonates undergoing surgery in several localities 18 19. Symptoms of persistent pain were identified in children breastfed with or without glucose14 16 and in children administered paracetamol12 16 18 27 and pentazocine (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Culture refers to a set of shared beliefs or values of a people group that are not genetically predetermined but are rather learned attributes (U.S. Department of Health and Human Services [USDHHS], 2001). In 2008, mothers in semiurban Nigeria were questioned on the presence of pain in infants, with 96% indicating that children less than 1 month of age could not experience pain (Olaogun, Ayandiran, Olalumade, Obiajunwa, & Adeyemo, 2008). Furthermore, Hastings (1995) showed that stoicism is the preferred response to postoperative pain in Kenya, as admission of pain is seen as weakness.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Parent/caregiver knowledge and attitudes on children's pain were identified as important aspects of paediatric pain management in LMIC. Olaogun, Ayandiran, Olalumade, Obiajunwa, and Adeyemo () and He, Jahja, et al () studied parent/caregiver's attitudes relating to children's pain, reporting lack of knowledge on pain management strategies as a hindrance in providing pain relief for their children. Also, He et al (; 2010) and Jongudomkarn et al () reported that parents often use non‐pharmacological strategies to alleviate their children's pain regardless of pain intensity.…”
Section: Resultsmentioning
confidence: 99%